Pulling together in a crisis? Anarchism, feminism and the limits of left-wing convergence in austerity Britain. (February 2016) - Maiguashca, Bice; Dean, Jonathan; Keith, Dan
In this article, we examine three key, recently emergent sites of anti-austerity activism in Britain – Left Unity, the People's Assembly and Occupy – in order to explore to what extent and in which ways the traditional British left is in the process of reconfiguring itself. More specifically, we explore the 'points of contact' being developed, or not, amongst feminist, anarchist and Marxist/socialist activists. We argue that if we are seeing a mutation of the left at present, it concerns a noticeable (if partial and contested) 'feminist turn' in terms of the composition, ideas and practices of these sites.